Diario el extra: perfil del lector y su posicionamiento en la ciudad de Riobamba, periodo octubre 2017 – marzo 2018 - Buenaño Urquizo, Danilo Javier (2018)
The objective of this research work was to identify the profile of the reader of the newspaper Extra and its positioning in the city of Riobamba. This research was based on the theory of uses and gratuities and on the contributions of Albán & Medina (2009), Celorio (2016), Checa (2003), Hernández (2011), whose studies helped to understand the consumption of the sensationalist press from the perspective of the popular reader. This work was carried out on the basis of a descriptive, non-experimental, bibliographic and field study, with a quantitative approach, which maintains the position of an empirical study established in the application of surveys, with multiple-choice questions, taking into account variables such as age, gender, level of study and social strata. Among the findings of the present investigation it was possible to know that the reader of the Extra newspaper belongs to a wide segment, among adults and young people, who maintain different occupations such as merchants, drivers, workers and students, etc. His reading preferences are for the sports and judicial section. This shows that sports and red chronicle content are the most attractive to the public. They are motivated by photographs and headlines. It is read more frequently every weekend, which generates an informative exhibition and social contract with the readers. Where their sole purpose is to keep you informed and entertained.